Prediction of tiers in the ranking of ice hockey players - Lehmus Persson, T.; Kozlica, H.; Carlsson, N.; Lambrix, P. (Machine Learning and Data Mining for Sports Analytics, 2020)
Many teams in the NHL utilize data analysis and employ data analysts. An important question for these analysts is to identify attributes and skills that may help predict the success of individual players. This study uses detailed player statistics from four seasons, player rankings from EA`s NHL video games, and six machine learning algorithms to find predictive models that can be used to identify and predict players` ranking tier (top 10%, 25% and 50%). We also compare and contrast which attributes and skills best predict a player`s success, while accounting for differences in player positions (goalkeepers, defenders and forwards). When comparing the resulting models, the Bayesian classifiers performed best and had the best sensitivity. The tree-based models had the highest specificity, but had trouble classifying the top 10% tier players. In general, the models were best at classifying forwards, highlighting that many of the official metrics are focused on the offensive measures and that it is harder to use official performance metrics alone to differentiate between top tier players.